PENGARUH BLOCKHOLDER OWNERSHIP DAN STRUKTUR AKTIVA TERHADAP STRUKTUR PEMBIAYAAN PADA PERUSAHAAN NON KEUANGAN GO PUBLIC DI BURSA EFEK INDONESIA - Suci Rachmawati (2013)
This research was conducted to examine the effect of variables Blockholder Ownership and the structure of assets toward the Structures of financing period 2012. The population number of 403 companies listed in Indonesia Stock Exchange 2012 period. The sampling technique used was purposive sampling. In order to obtain a total sample of 48 companies. Data were obtained from published financial statements of the Indonesia Stock Exchange website is www.idx.co.id. The analysis technique used here is multiple linear regressionand hypothesis test using t-statistic and F-statistic with level of significance 5%. These results indicate that simultaneous variables Blockholder Ownership and the structure of assets significantly influence the Structures of financing. While the results of research conducted partially Blockholder Ownership not significant effect on the Structures of financing and the structure of assets significant effect on the Structures of financing.